Revelation of ZnS Nanoparticles Induces Follicular Atresia and Apoptosis in the Ovarian Preovulatory Follicles in the Catfish Mystus tengara (Hamilton, 1822) - Nilanjana Chatterjee; Baibaswata Bhattacharjee (Scientifica)
Important physicochemical characteristics of water like dissolved oxygen content, pH, and so forth were found to change in a dose dependent manner, showing a negative correlation with the nanoparticle concentration, when ZnS nanoparticle (NP) was exposed to water. This observation could be attributed to the enhanced photooxidation property associated with ZnS in its NP form. Under this situation, the catfish Mystus tengara was forced to live in hypoxia in its habitat. This condition was found to hamper the natural oogenesis process of the fish. Due to exposure at relatively lower concentration of ZnS NPs (250 μg/L), most of the maturing follicles of M. tengara failed to complete the process of vitellogenesis properly and underwent preovulatory atresia followed by oocytic apoptosis. For relatively higher concentration of ZnS nanoparticles (500 μg/L), the previtellogenic process continued with increasing number of apoptotic cells; however the vitellogenic process was found to be totally blocked. This unusual reproductive behaviour in female M. tengara can be attributed to the decreased metabolism of the fishes under ZnS nanoparticle induced hypoxia.